Synergy of Policy and Cultural Economy: Practical Implementation of Regional Regulation No. 2 of 2021 in Strengthening Local Identity and Economy in South Sumatra - Andi Novriansyah; Alfitri; Andries Lionardo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Local cultural heritage is an integral part of a region's identity, enriching Indonesia's cultural diversity as a whole. This study aims to explore the efforts of the South Sumatra Government to preserve local cultural heritage in the province by implementing Regional Regulation (Perda) Number 2 of 2021 concerning the Architecture of Buildings with Regional Identity Ornaments. This policy stipulates requirements for incorporating elements of local wisdom, particularly Songket and Tanjak motifs, into various building structures such as government buildings, schools, toll gates, train stations, terminals, and even airports managed by Regional Apparatus Organizations (OPD) in the region. This study uses a qualitative approach by collecting data through in-depth interviews with government officials directly involved in policy implementation. Data analysis was conducted using a descriptive approach to evaluate the policy and its implementation practices in the field. The research findings indicate that the implementation of Perda Number 2 of 2021 has been successful and effective, generating a significant impact on efforts to preserve local cultural heritage in South Sumatra. This policy encourages each Regional Apparatus Organization (OPD) to incorporate regional ornamentation into building structures, such as government offices, schools, state-owned enterprises (BUMN/BUMD), hospitals, regional military (KODAM/Kodim), and the Regional Police Chief's office. Furthermore, this policy allocates specific funds for renovations related to local wisdom, particularly in the application of Songket motifs. In conclusion, Regional Regulation No. 2 of 2021 provides a solid foundation for the preservation of local cultural heritage in South Sumatra. By promoting the integration of elements of local wisdom into public building structures, this policy strengthens regional cultural identity while supporting sustainable development. The implications of this policy also reflect the regional government's commitment to preserving local cultural values ​​in regional planning and development.